The Effect Guide Imagery (Five Fingers Hypnosis) Toward Decreasing Of Anxiety To The Quarantine Isolation Patient In Covid-19 - I Komang Pasek Ari Putra Jaya; Puji Purwaningsih; Fiktina Vivri Ismiriyam; Endang Susilowati (KLASICS, 2021)
Abstract. COVID-19 is a disease caused by the corona virus. COVID-19 has a negative impact on all fields, especially in the health sector, both biologically and psychologically. One of the psychological disorders as a result of the COVID-19 pandemic is anxiety. Participants in the COVID-19 quarantine are a group that has been confirmed positive for COVID-19 with OTG status, this group is at high risk of experiencing psychological disorders, namely anxiety because of concerns about the impact that will be caused by the corona virus. Purpose this study was to determine the effect of providing guide imagery (five finger hypnosis) on reducing anxiety in participants undergoing quarantine in the COVID-19 isolation unit in Bali Province. This study uses quantitative methods, the research design used is Quasy Experiment or quasi-experimental, with a non-equivalent approach (pretest and posttest) control group design. The populations of this study were 52 quarantine participants in the COVID-19 isolation unit. The sampling technique used total sampling method with a sample size of 52 respondents. The measuring instrument used was the HARS (Hamilton Anxiety Rating Scale) questionnaire. Data analysis used the Wilcoxon test. The study found that there was a difference in the mean level of anxiety before and after being given five-finger hypnosis therapy, the average level of anxiety before being given the intervention was 2.38 down to 1.79 after being given the intervention. The p-value = 0.000 (α = 0.05). There is an effect on providing guide imagery (five-finger hypnosis) on reducing anxiety in participants who are undergoing quarantine in the COVID-19 isolation unit in Bali province.